2016
DOI: 10.1371/journal.pntd.0004422
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-10 and TGFβ from CD4+CD25+FoxP3+ T Cells Correlates with Parasite Load in Indian Kala-azar Patients Infected with Leishmania donovani

Abstract: BackgroundVisceral leishmaniasis (VL) is distinguished by a complex interplay of immune response and parasite multiplication inside host cells. However, the direct association between different immunological correlates and parasite numbers remains largely unknown.Methodology/Principal FindingsWe examined the plasma levels of different disease promoting/protective as well as Th17 cytokines and found IL-10, TGFβ and IL-17 to be significantly correlated with parasite load in VL patients (r = 0.52, 0.53 and 0.51 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 58 publications
3
44
0
1
Order By: Relevance
“…As described previously, immunosuppressive factors that affect acquired cellular immunity, such as age, gender, HIV infection status and nutrition status, seem to be associated with higher levels of parasitemia, which appear to be driven by the production of IL-10 and TGF-b, thereby inhibiting the production of c-interferon by T-cells [63,64]. Recently, Battacharya et al [23] showed that CD4+CD25+FoxP3+ T-regulatory cells were strongly associated with the parasite burden. After this immunosuppression, innate progressive systemic inflammation following an increasing parasite burden inside macrophages may initiate the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…As described previously, immunosuppressive factors that affect acquired cellular immunity, such as age, gender, HIV infection status and nutrition status, seem to be associated with higher levels of parasitemia, which appear to be driven by the production of IL-10 and TGF-b, thereby inhibiting the production of c-interferon by T-cells [63,64]. Recently, Battacharya et al [23] showed that CD4+CD25+FoxP3+ T-regulatory cells were strongly associated with the parasite burden. After this immunosuppression, innate progressive systemic inflammation following an increasing parasite burden inside macrophages may initiate the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, Battacharya et al . showed that CD4+CD25+FoxP3+ T‐regulatory cells were strongly associated with the parasite burden. After this immunosuppression, innate progressive systemic inflammation following an increasing parasite burden inside macrophages may initiate the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visceral organs are well-known homing organs of parasites [3]. Few studies from this viewpoint have been carried out using peripheral blood [21]. Suppression of the T cell response in VL is well demonstrated, and contributes to the dissemination of parasites in various visceral organs of reticulo-endothelial organs.…”
Section: Discussionmentioning
confidence: 99%
“…To address some of these issues, we focused our attention on the T effector and T reg cells in the BM of VL patients with HPL as opposed to LPL patients. Few studies from this viewpoint have been carried out using peripheral blood [21]. However, a correlation between immune parameters with parasitic load at the BM remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%